REGULARITIES OF THE COURSE OF THE PROCESSES OF PSYCHOPHYSIOLOGICAL ADAPTATION AMONG PUPILS OF SENIOR SCHOOL AGE WITH DIFFERENT LEVELS OF HEALTH - Mostova, Olha; Stoyan, Natalya; Bratkova, Olha; Dudarenko, Oksana; Drezhenkova, Inna; Serheta, Ihor (European Science, 2023)
In the course of the conducted research, the patterns of psychophysiological adaptation processes among pupils of senior school age with different levels of health were determined. 120 girls and 108 boys (or 10.3% of the total number of examined) were inc